Pengaruh Kebijakan Kompensasi Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Hotel Kawana Padang - Amesha Farras; Rita Srihasnita (CV. ITTC INDONESIA, 2025)
This study aimed to determine the influence of compensation policies and the work environment on employee job satisfaction at the Kawana Hotel. The study was conducted at the Kawana Hotel with a sample of 54 respondents. The research employed a quantitative method with a descriptive approach. The data sources used were primary and secondary data, using a questionnaire as a data collection technique. The sample in this study used a saturated sampling method. Hypothesis testing used in this study was multiple linear regression analysis using the IBM SPSS 23 statistical tool. The results showed that (1) compensation policies have a positive and significant effect on employee job satisfaction, (2) the work environment has a positive and significant effect on employee job satisfaction, and (3) compensation policies and the work environment simultaneously have a positive and significant effect on employee job satisfaction.